Validity and reliability of the Turkish version of the Smart Phone Application Based Addiction Scale - Mehmet Enes Gokler; Yunus Emre Bulut (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
The aim of the study was to determine the validity and reliability of the Turkish version of Smart Phone Application Based Addiction Scale (SABAS). The study was conducted among people who work in Ankara Provincial Health Directorate. Total 413 people were participated to the study, more than half of the participants were female (66.3%), the mean age was 40.87±7.96 years (range, 23-63) years. The mean score of SABAS was 15.22±6.94 (range 6-36). The scores obtained from SABAS decreased with increasing age (r=0.163; p=0.001) and did not change according to gender (Z=0.982; p=0.332). According to the Kaiser-Meyer-Olkin (KMO) criteria, the size of the correlation coefficients and the correlation coefficients were correlated with the factor analysis (KMO=0.867, p [JCBPR 2019; 8(2.000): 100-106]